Compound Instability Effect and Countermeasures of Pit-in-Pit in Collapsible Loess Strata - Jiawei Xu; Peilong Yuan; Jinxing Lai; Peiyao Che; Xiangcheng Su; Xulin Su (Applied Sciences, 2025)
The construction of pit-in-pit has become increasingly challenging due to the bad geological conditions, particularly in collapsible loess strata. To understand its supporting characteristics and failure mode, it is necessary to study the composite instability mechanism in the loess strata. This research systematically investigates the interacting instability modes of pit-in-pit under a collapsible loess stratum, studies the effects of different reinforcement parameters through physical model tests, analyzes the significance level of each reinforcement factor, and monitors the displacement of the foundation pit during construction in a pit project in Zhengzhou. The result shows that the soil pressure distribution law of the pit in a collapsible loess formation is a complex function of soil parameters, the relative positional relationship between the inner and outer foundation pits, and the time of immersion. The model test shows that the width and depth of reinforced soil have the most significant influence. The reinforcement measures proposed in this paper can effectively control the displacement of each measuring point during the foundation pit excavation, which can provide a reference for similar projects.